A computational approach based on a multiaxial fatigue criterion combining phase transformation and shakedown response for the fatigue life assessment of Nitinol stents. (November 2018) - Scalet, Giulia; Menna, Costantino; Constantinescu, Andrei; Auricchio, Ferdinando
Self-expanding stents made of Nitinol, a Nickel–Titanium shape memory alloy, are used in standard medical implants for the treatment of cardiovascular diseases. Despite the increasing success, clinical studies have reported stent failure after the deployment in the human body, thus undermining patient's safety and life. This study aims to fill the gap of reliable assessment of the fatigue life of Nitinol stents. We propose a global computational design method for preclinical validation of Nitinol stents, which can be extended to patient-specific computations. The proposed methodology is composed of a mechanical finite element analysis and a fatigue analysis. The latter analysis is based on a novel multiaxial fatigue criterion of the Dang Van type, combining the shakedown response of the stent and the complexity of phase transformation taking place within the material. The method is implemented in the case of a carotid artery stent. The implant configuration as well as the applied cyclic loading are shown to affect material phase evolution as well as stent lifetime. The comparison with the results obtained by applying a strain-based constant-life diagram approach allows to critically discuss both fatigue criteria and to provide useful recommendations about their applicability.